PERAN PENYULUH PERTANIAN DALAM PENERAPAN BUDIDAYA PADI ORGANIK DENGAN METODE SRI (SYSTEM RICE OF INTENSIFICATION) DI KOTA TARAKAN - Rayhana Jafar; Sulton Alimin (J-PEN Borneo : Jurnal Ilmu Pertanian, 2019)
ABSTRACT Counseling is one of the important things in providing knowledge to farmers as a process of disseminating information, information processes or providing explanations, the process of changing farmers' behavior (attitudes, knowledge and skills) and the educational process. The importance of the role of agricultural extension workers, especially in the application of organic rice cultivation using the SRI (System of Rice Intensification) method in Tarakan City is still very much needed to improve human resources (farmers) so that they are able to manage existing natural resources intensively in order to achieve productivity and income improvement activities. The purpose of this study was to describe the role of agricultural extension agents in the application of the SRI method in the Mamburungan Village of Tarakan City and to find out the obstacles faced by agricultural extension workers in extension activities to farmer groups in Mamburungan Village, Tarakan City. This research is a qualitative descriptive study with a survey method. This research is analyzed by using descriptive analysis and Likert Scale. Determination of samples using purposive sampling technique. The results of the study show the role of agricultural instructors in the application of the SRI method in Mapan Sejahtera farmer groups as facilitators, motivators, educators and communicators are categorized as very important. The obstacle faced by extension agents in conducting extension activities is the lack of farmers' participation in developing organic rice cultivation with the SRI system because farmers are still focused on conventional rice cultivation; facilities and infrastructure in conducting extension activities are still very minimal so that the process of extension activities is hampered. Key words: Extension, Role of Extension, SRI Method ABSTRAK Penyuluhan merupakan salah satu hal yang penting dalam memberikan pengetahuan kepada para petani sebagai proses penyebarluasan informasi, proses penerangan atau memberikan penjelasan, proses perubahan prilaku petani (sikap, pengetahuan dan keterampilan) dan proses pendidikan. Pentingnya peran penyuluh pertanian khususnya dalam penerapan budidaya padi organik dengan metode SRI (System of Rice Intensification) di Kota Tarakan masih sangat dibutuhkan  untuk meningkatkan SDM (petani)  sehingga mampu mengelola sumber daya alam yang ada secara intensif demi tercapainya kegiatan peningkatan produktivitas dan pendapatan. Tujuan penelitian ini adalah untuk mendeskripsikan peran penyuluh pertanian dalam penerapan metode SRI di Kelurahan Mamburungan Kota Tarakan dan mengetahui kendala yang dihadapi oleh penyuluh pertanian dalam kegiatan penyuluhan pada kelompok tani di Kelurahan Mamburungan Kota Tarakan. Penelitian ini adalah penelitian deskriptif kualitatif dengan metode survei. Metode analisis data yang digunakan adalah deskriptif dan Skala Likert. Penentuan sampel dengan menggunakan teknik purposive sampling. Hasil penelitian menunjukkan peran penyuluh pertanian dalam penerapan metode SRI di kelompok tani Mapan Sejahtera sebagai fasilitator, motivator, edukator dan komunikator dikategorikan sangat berperan. Kendala yang dihadapi penyuluh dalam melakukan kegiatan penyuluhan adalah  kurangnya partisipasi petani dalam pengembangan budidaya padi organik dengan sistem SRI karena  petani masih terfokus dengan budidaya padi secara konvensional; sarana dan prasarana dalam melakukan kegiatan penyuluhan masih sangat minim sehingga mengakibatkan proses kegiatan penyuluhan terhambat. Kata kunci: Penyuluh, Peran Penyuluh, Metode SRI (System of Rice Intensification)